2021
DOI: 10.1186/s12987-021-00243-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mechanisms of ventricular enlargement in idiopathic normal pressure hydrocephalus: a role of cerebrospinal fluid dynamics and motile cilia

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is considered an age-dependent chronic communicating hydrocephalus associated with cerebrospinal fluid (CSF) malabsorption; however, the aetiology of ventricular enlargement in iNPH has not yet been elucidated. There is accumulating evidence that support the hypothesis that various alterations in CSF dynamics contribute to ventricle dilatation in iNPH. This review focuses on CSF dynamics associated with ventriculomegaly and summarises the current literature based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 99 publications
1
20
1
Order By: Relevance
“…Challenging to traditional CSF physiology, increasing investigations raise the new concept of CSF dynamics that, rather than choroid plexus, CSF production also comes from the interstitial fluid efflux, and the major CSF outflow pathway may go through the lymphatic drainages rather than dural venous sinuses through arachnoid villi ( Louveau et al, 2016 ; Da Mesquita et al, 2018 ; Louveau et al, 2018 ; Mestre et al, 2018 ; Ringstad and Eide, 2020 ; Yamada et al, 2021 ). The CSF outflow through lymphatic drainages mainly goes through the subarachnoid spaces to the meningeal lymphatics and cervical lymphatics via the cribriform plate and nasal lymphatics ( Proulx, 2021 ).…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenging to traditional CSF physiology, increasing investigations raise the new concept of CSF dynamics that, rather than choroid plexus, CSF production also comes from the interstitial fluid efflux, and the major CSF outflow pathway may go through the lymphatic drainages rather than dural venous sinuses through arachnoid villi ( Louveau et al, 2016 ; Da Mesquita et al, 2018 ; Louveau et al, 2018 ; Mestre et al, 2018 ; Ringstad and Eide, 2020 ; Yamada et al, 2021 ). The CSF outflow through lymphatic drainages mainly goes through the subarachnoid spaces to the meningeal lymphatics and cervical lymphatics via the cribriform plate and nasal lymphatics ( Proulx, 2021 ).…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%
“…Based on the new CSF dynamic concept, the pathogenic mechanisms of iNPH or communicating hydrocephalus that correlate with the alterations in motile cilia and cerebrospinal fluid dynamics have been extensively investigated, and the related mutant genes have also been reported ( Table 2 ). The mutant genes related to motile cilium dysfunction on ependymal cells, and consequent hydrocephalus development may include Ccdc39 , Celsr2 , Celsr3 , Cetn2 , Dvl , Foxj1 , Hydin , Mdnah5 , Pkd1 , Tg737 , Daple , Dnah14 , Cfap43 , Cwh43 , Eml1 , Fmn2 , Tmem67 , and Zcchc8 ( Law et al, 2014 ; Shaheen et al, 2017 ; Kundishora et al, 2021 ; McKnight et al, 2021 ; Yamada et al, 2021 ). For example, Foxj1 mutation results in ciliopathy and hydrocephalus due to dysfunction of motile cilia ( Abdi et al, 2018 ; Wallmeier et al, 2019 ).…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of ventricular enlargement on CT or MRI is essential for the diagnosis of iNPH. Although the etiology of ventricular enlargement in iNPH has not yet been elucidated, the total amount of intracranial CSF volume increases due to CSF malabsorption ( 41 ). The historically used Evans index >0.3 is defined as the maximum width of both frontal horns of the lateral ventricles divided by the maximum intracranial width on the same slice on CT or MRI.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…Recently, a more severe PCD phenotype in humans was reported, known as 'reduced generation of multiple motile cilia' (RGMC) involving mutations in the multicilin gene which is linked to a high incidence of hydrocephalus and choroid plexus hyperplasia [26,27]. Notably, studies have shown that the CSF stroke volume and the oscillatory shear stress in the cerebral aqueduct increase in normal pressure hydrocephalus (NPH) which impede normal cilia beating [28][29][30]. Furthermore, a study using dynamic contrast enhanced MRI (DCE-MRI) with CSF administration of a Gd-based tracer showed that glymphatic clearance was reduced in human patients with NPH [31,32] suggesting a potential link between impaired glymphatic clearance, cilia dysfunction and hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%